A new species of Heredius (Hymenoptera: Braconidae: Doryctinae) from Brazilian Amazon Rainforest - Antonielson B. Silva; Eduardo M. Shimbori; Daniell R.R. Fernandes (Zoologia (Curitiba))
ABSTRACT Heredius Marsh, 2002 is a small genus, with only three described species, recorded only in Costa Rica and Brazil. The aim of this paper was to describe a new species of Heridius from Brazilian Amazon Rainforest. The specimen was collected by Malaise trapping in the Adolpho Ducke Forest Reserve (02°57’S, 59°55’W), Manaus, Amazonas, Brazil. A new species, Heredius gadelhai sp. nov. differs from the other three known species mainly having 1.5 mm long, is entirely yellow, ocellar-ocular distance of about 3.5 times the diameter of the lateral ocellus; malar space 0.3 times the height of the eye; first flagellomere 0.8 times the length of the second flagellomere; precoxal groove present and smooth, and ovipositor 0.2 times the length of the body. We illustrate and a key to all described species of Heredius were provided.